Cigarette Smoking on Severity of Primary Angle Closure Glaucoma in Malay Patients. Issue 1 (January 2019) - Niven, Teh Chong Seong; Azhany, Yaakub; Rohana, Abdul J.; Karunakar, Tirmandas V.N.; Thayanithi, Sandragasu; Jelinar Noor, Mohd N.; Norhalwani, Husain; Zuraidah, Mustari; Siti Azrin, Ab H.; Ahmad, Mt S.; Aung, Tin; Liza-Sharmini, Ahmad T.
Abstract : Purpose: The purpose of this study was to determine the association between cigarette smoking and the severity of primary angle closure glaucoma (PACG) in Malay patients residing in Malaysia. Methods: A cross-sectional study was conducted involving 150 Malay PACG patients between April 2014 and August 2016. Ocular examination was performed including Humphrey visual field (HVF) 24-2 analysis assessment. On the basis of the 2 consecutive reliable HVFs, the severity of glaucoma was scored according to modified Advanced Glaucoma Intervention Study (AGIS) by 2 masked investigators and classified as mild, moderate, and severe. Those with retinal diseases, neurological diseases, memory problem, and myopia ≥4 diopters were excluded. Their smoking status and details were obtained by validated questionnaire from Singapore Malay Eye Study (SiMES). The duration of smoking, number of cigarettes per day, and pack/year was also documented. Multiple linear regression analysis was conducted. Results: There was a significant association between education level and severity of PACG ( P =0.001). However, there was no significant association between cigarette smoking and severity of glaucoma ( P =0.080). On the basis of multivariate analysis, a linear association was identified between cigarette smoked per day (adjusted b =0.73; 95% CI: 0.54, 1.45; P <0.001) and body mass index (adjusted b =0.32; 95% CI: 0.07, 1.35; P =0.032) with AGIS score. Conclusions: There was no significant association between cigarette smoking and severity of PACG. Cigarette smoked per day among the smokers was associated with severity of PACG. However, because of the detrimental effect of smoking, cessation of smoking should be advocated to PACG patients.